Decellularized umbilical cord stroma in tissue engineering and regenerative medicine: a systematic review - Yu. B. Basok; A. A. Kondratenko; L. I. Kalyuzhnaya; E. A. Volkova; K. A. Vorobyov; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2023)
Despite great progress in the field of biomaterials for tissue engineering and regenerative medicine, the high requirements placed on artificial matrices (matrices, carriers, scaffolds) are the reason for the ongoing search for natural or synthetic extracellular matrix mimetics. Among such materials, decellularized umbilical cord (UC) stroma appears to be very attractive – it has a high content of hyaluronic acid, cytokines, and growth factors, and there are no ethical restrictions for its production. Decellularized UC stroma has been found to promote cartilage, liver tissue and nerve tissue repair, as well as wound healing. The review critically analyzes and summarizes published data on the ability of decellularized UC stroma to maintain the necessary conditions for adhesion, migration, differentiation and functional activity of adherent cells, thus stimulating the internal (physiological) regenerative potential of tissues. Literature was searched for in the following electronic databases: Medline/PubMed (www/ncbi. nlm.nih.gov/pubmed), Cochrane library (https://www.cochrane.org), and eLIBRARY/Russian Science Citation Index (https://www.elibrary.ru). Inclusion criteria were the presence of biomaterials obtained from decellularized human UC stroma. Exclusion criteria for papers included research objects as decellularized umbilical cord vessels (veins and arteries) and umbilical cord cell cultures. Twenty-five original articles in English and Russian were selected for analysis of the products obtained, their applications, decellularization methods and research results. The review also discusses the prospects for decellularized umbilical cord in medicine.